Coronary Artery Fistulae Discovered during Presentation of a Patient Having Heart Failure due to Severe Aortic Stenosis - Abdulrahman Khalifa Alammar (Case Reports in Cardiology)
Introduction. Coronary artery fistulae (CAF) are rare defects with abnormal communication between a coronary artery with either a cardiac chamber or another vascular structure, bypassing the myocardial capillary network. We report a rare multiple arterial coronary fistulae with drainage to the right pulmonary artery. Case Presentation. A 56-year-old male was brought to our hospital for work-up of severe aortic stenosis. Further evaluation revealed multiple CAF with abnormal drainage to the right pulmonary artery. He was discharged after aortic valve replacement and closure of the coronary fistula. Conclusion. This case demonstrates that patients with complex CAF and drainage to the right pulmonary artery can remain asymptomatic and diagnosed accidentally during cardiac imaging, presenting particular challenges in both medical and surgical treatment.